Customer referencing and capital market benefits: Evidence from the cost of equity - Jing, Jiao; Myers, Linda A.; Ng, Jeffrey; Su, Lixin (Nancy) (Contemporary accounting research, 2023)
Customer referencing is a strategy that firms can use to disclose their connections with reputable customers as a means of enhancing their own reputations. We study the capital market benefits of naming reputable nonmajor customers in firms' financial reports to provide empirical evidence on whether this form of customer referencing has important practical implications. We predict and find that firms enjoy a lower cost of equity when they engage in customer referencing in their financial reports, consistent with the argument that this form of voluntary disclosure increases investor attention and customer certification. In cross‐sectional analyses, we predict and find that the benefits of customer referencing are more pronounced for firms that (1) lack major customers or reputable major customers, (2) name customers whose reputations exceed their own, and (3) face higher competition. Overall, our study provides evidence that communicating certain interorganizational connections can generate capital market benefits for disclosing firms. Résumé Référencement de la clientèle et avantages liés au marché financier : données probantes associées au coût des fonds propres Le référencement de la clientèle est une stratégie que les entreprises peuvent utiliser pour révéler leurs liens avec des clients respectables afin d'améliorer leur propre réputation. Nous étudions les avantages sur le marché financier que procure la mention de clients respectables, sans qu'ils soient des clients de premier plan, dans les rapports financiers des entreprises pour dégager des données empiriques indiquant si ce type de référencement a d'importantes conséquences pratiques. Nous prédisons et établissons que les entreprises profitent d'un coût de fonds propres moins élevé lorsqu'ils nomment des clients dans leurs rapports financiers, conformément à l'argument voulant que ce type de divulgation volontaire accroisse l'attention portée par les investisseurs ainsi que la certification par la clientèle. Dans le cadre d'analyses transversales, nous prédisons et montrons que les avantages du référencement de la clientèle sont plus prononcés pour les entreprises qui (1) n'ont pas de clients de premier plan ou de clients de premier plan respectables, (2) nomment des clients dont la réputation surpasse la leur et (3) font face à une plus forte concurrence. Dans l'ensemble, notre étude fournit des données probantes indiquant que la divulgation de certains liens interorganisationnels peut procurer des avantages liés au marché financier.